Mid-Holocene charcoal morphotype data from Sea of Galilee, northern Israel - Andrea Miebach (PANGAEA, 2023)
The dataset encompasses a high-resolution macro-charcoal time series from the Sea of Galilee dating to the mid-Holocene before and during the first olive cultivation. With a two-year-resolution, the data offers one of the highest resolution sedimentary charcoal records yet available worldwide. A well-dated sediment section of a lacustrine sediment core that were drilled at the center of the lake in 2010 was subsampled into contiguous 0.5 cm samples. The here provided charcoal raw data categorized into distinct charcoal morphotypes was the base for quantitative analyses indicating changes in fire regimes and sources of biomass burning in northern Israel. It gained insights into the role of fire in early olive horticulture.